PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN PAKU SISIK NAGA (DRYMOGLOSSUM PILOSELLOIDES L.PRESL) TERHADAP PEROKSIDASI LIPID HATI PADA TIKUS JANTAN GALUR WISTAR YANG DIINDUKSI CCL4 - Malinda, Ayu Fauzia; Fatimawali, Fatimawali; Yudistira, Adithya (PHARMACON, 2013)
The aims of this research was to determine the effect of ethanol extract paku sisik nagaleaves against lipid peroxidation in male wistar liver induced by CCl4. Method of thisresearch used laboratory experiment using 9 white male wistar were divided into 3 treatmentgroups. All groups were given treatment during ten days. The first group (negative control)was given distilled water ad libitum, the second group was given ethanol extract of paku sisiknaga leaves 97.02 mg/kg body weight per oral and the third group (positive control) wasgiven Curcuma 45 mg/kg body weight per oral. On the tenth day, after two hours oftreatment all groups were given CCl4 1mL/kg body weight intraperitonial, eighteen hoursafter that rats in all groups were dissected and taken his liver. Then rat liver analyzed byTBARS method (Thiobarbiturate Acid Reactive Subtance) to measure the levels of MDA(Malondialdehyde) which is an indicator of lipid peroxidation in the rat liver. Data wereanalyzed by SPSS ver.20, significant difference between treatments was tested by one-wayANOVA. The results showed a significant difference with 95% confidence level (Î± = 0.05)with a mean value of MDA 3,828 Î¼M negative control group, group of ethanol extract ofpaku sisik naga leaf was 2,666 Î¼M and 2,211 Î¼M for positive control group. Ethanol extractof paku sisik naga leaves with dose 97.02 mg/kg body weight can prevent the process of lipidperoxidation in rat liver.Keywords: Drymoglossum piloselloides L. Presl, CCl4, TBARS, lipid peroxidation